THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) AND THINK-PAIR-SHARE (TPS) MODELS ON READING COMPREHENSION OF NARRATIVE TEXT - Berliana, Ainun; Forsia, Lastry; -, Purnawati (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the significant influence of the CIRC and TPS models on students' reading comprehension of narrative texts at SMKN 8 Tangerang Regency. To achieve this, a quantitative method with a quasi-experimental design was employed. The study used three classes: two as experimental classes and one as a control class. The first experimental class used the TPS method, the second used the CIRC method, and the control class used conventional models. The data analysis in this study used an independent t-test and an ANOVA test. The results of this study indicated that there was an increase in reading comprehension from the third grade. However, the two experimental classes improved better than the control class, with the post-test score of the experimental class using TPS at 75.97 and the post-test result using the CIRC method at 76.17.Meanwhile, the results of the post-test of the control class were 65.46.for the results of hypothesis analysis of the TPS class method using an independent t-test, a significance value of 0.004 was obtained, the CIRC method class was 0.002, and for the ANOVA hypothesis test, a significance value of 0.002 was obtained. The TPS and CIRC models significantly influence reading comprehension in grade ten at SMKN 8 Tangerang Regency. Therefore, this research is expected to provide implications for applying the Think-Pair-Share (TPS) and Cooperative Integrated Reading and Composition (CIRC) models in improving students' reading ability in high school/equivalent in Indonesia.